d ‐canavanine affects peptidoglycan structure, morphogenesis and fitness in Rhizobiales - Alena Aliashkevich; Matthew Howell; Pamela J. B. Brown; Felipe Cava (Environmental Microbiology, 2021)
Summary The bacterial cell wall is made of peptidoglycan (PG), a polymer that is essential for maintenance of cell shape and survival. Many bacteria alter their PG chemistry as a strategy to adapt their cell wall to external challenges. Therefore, identifying these environmental cues is important to better understand the interplay between microbes and their habitat. Here, we used the soil bacterium Pseudomonas putida to uncover cell wall modulators from plant extracts and found canavanine (CAN), a non‐proteinogenic amino acid. We demonstrated that cell wall chemical editing by CAN is licensed by P. putida BSAR, a broad‐spectrum racemase which catalyses production of dl ‐CAN from l ‐CAN, which is produced by many legumes. Importantly, d ‐CAN diffuses to the extracellular milieu thereby having a potential impact on other organisms inhabiting the same niche. Our results show that d ‐CAN alters dramatically the PG structure of Rhizobiales (e.g., Agrobacterium tumefaciens , Sinorhizobium meliloti ), impairing PG crosslinkage and cell division. Using A. tumefaciens , we demonstrated that the detrimental effect of d ‐CAN is suppressed by a single amino acid substitution in the cell division PG transpeptidase penicillin binding protein 3a. Collectively, this work highlights the role of amino acid racemization in cell wall chemical editing and fitness.

The role of conserved proteins DrpA and DrpB in nitrate respiration of Thermus thermophilus - Zahra Chahlafi; Laura Alvarez; Felipe Cava; José Berenguer (Environmental Microbiology, 2018)
Summary In many Thermus thermophilus strains, nitrate respiration is encoded in mobile genetic regions, along with regulatory circuits that modulate its expression based on anoxia and nitrate presence. The oxygen‐responsive system has been identified as the product of the dnrST ( dnr ) operon located immediately upstream of the nar operon ( narCGHJIKT ), which encodes the nitrate reductase (NR) and nitrate/nitrite transporters. In contrast, the nature of the nitrate sensory system is not known. Here, we analyse the putative nitrate‐sensing role of the bicistronic drp operon ( drpAB ) present downstream of the nar operon in most denitrifying Thermus spp. Expression of drp was found to depend on the master regulator DnrT, whereas the absence of DrpA or DrpB increased the expression of both DnrS and DnrT and, concomitantly, of the NR. Absence of both proteins made expression from the dnr and nar operons independent of nitrate. Polyclonal antisera allowed us to identify DrpA as a periplasmic protein and DrpB as a membrane protein, with capacity to bind to the cytoplasmic membrane. Here, we propose a role for DrpA/DrpB as nitrate sensors during denitrification.

Environmental roles of microbial amino acid racemases - Sara B. Hernández; Felipe Cava (Environmental Microbiology, 2016)
Summary Enzymes catalysing the stereo‐chemical inter‐conversion of amino acids are known as amino acid racemases. In bacteria, these enzymes are fundamental to synthesize the D ‐ A la and D ‐ G lu that are critical components of the peptidoglycan. In addition to this structural function in cell wall assembly, D ‐amino acids produced by microbial amino acid racemases have been described as relevant constituents in other prokaryotic structures (e.g. capsule, non‐ribosomal peptides) and have been associated to growth fitness and to processes such as biofilm development, spore germination and signalling. The recent discovery of broad spectrum racemases able to produce and release several D ‐amino acids to the environment suggests that these enzymes might have a great impact in microbial ecology. Consequently, new data on the biochemistry and regulation of racemases is key to understand the biological significance of D ‐enantiomers in nature, in particular their effect on microbial social networks. This review summarizes current knowledge on the environmental roles of bacterial racemases with an emphasis on the potential roles of the new broad spectrum enzymes in natural environments.

Bile‐induced peptidoglycan remodelling in S almonella enterica - Sara B. Hernández; Felipe Cava; M. Graciela Pucciarelli; Francisco García‐del Portillo; Miguel A. de Pedro; Josep Casadesús (Environmental Microbiology, 2015)
Summary Changes in the peptidoglycan ( PG ) structure of S almonella enterica are detected in the presence of a sublethal concentration of sodium deoxycholate ( DOC ): (i) lower proportions of B raun lipoprotein ( Lpp )‐bound muropeptides; (ii) reduced levels of muropeptides cross‐linked by L (meso)‐diaminopimelyl‐ D (meso)‐diaminopimelic acid ( L ‐ D ) peptide bridges (3‐3 cross‐links). Similar structural changes are found in S . enterica cultures adapted to grow in the presence of a lethal concentration of DOC , suggesting that reduced anchoring of B raun protein to PG and low occurrence of 3‐3 cross‐links may increase S . enterica resistance to bile. This view is further supported by additional observations: (i) A triple mutant lacking L , D ‐transpeptidases YbiS , ErfK , and YcfS , which does not contain Lpp anchored to PG , is hyper‐resistant to bile; (ii) enhanced 3‐3 cross‐linking upon overexpression of YnhG transpeptidase causes a decrease in bile resistance. These observations suggest that remodelling of the cell wall may be added to the list of adaptive responses that permit survival of S . enterica in the presence of bile.

A D , D ‐carboxypeptidase is required for V ibrio cholerae halotolerance - Andrea Möll; Tobias Dörr; Laura Alvarez; Brigid M. Davis; Felipe Cava; Matthew K. Waldor (Environmental Microbiology, 2015)
Summary The biological roles of low molecular weight penicillin‐binding proteins ( LMW PBP ) have been difficult to discern in G ram‐negative organisms. In E scherichia coli , mutants lacking these proteins often have no phenotype, and cells lacking all seven LMW PBPs remain viable. In contrast, we report here that V ibrio cholerae lacking DacA ‐1, a PBP 5 homologue, displays slow growth, aberrant morphology and altered peptidoglycan ( PG ) homeostasis in Luria–Bertani ( LB ) medium, as well as a profound plating defect. DacA ‐1 alone among V . cholerae's LMW PBPs is critical for bacterial growth; mutants lacking the related protein DacA ‐2 and/or homologues of PBP 4 or PBP 7 displayed normal growth and morphology. Remarkably, the growth and morphology of the dac A ‐1 mutant were unimpaired in LB media containing reduced concentrations of N a C l (100 mM or less), and also within suckling mice, a model host for the study of cholera pathogenesis. Peptidoglycan from the dac A ‐1 mutant contained elevated pentapeptide levels in standard and low salt media, and comparative analyses suggest that DacA ‐1 is V . cholerae's principal DD ‐carboxypeptidase. The basis for the dac A ‐1 mutant's halosensitivity is unknown; nonetheless, the mutant's survival in biochemically uncharacterized environments (such as the suckling mouse intestine) can be used as a reporter of low N a + content.

Thermus thermophilus as biological model - Felipe Cava; Aurelio Hidalgo; José Berenguer (Extremophiles, 2009)

Expression and use of superfolder green fluorescent protein at high temperatures in vivo : a tool to study extreme thermophile biology - Felipe Cava; Miguel Angel De Pedro; Emilio Blas‐Galindo; Geoffrey S. Waldo; Lars F. Westblade; José Berenguer (Environmental Microbiology, 2008)
Summary Superfolder GFP (sGFP) is a variant of the Green Fluorescent Protein that folds efficiently when fused to poorly folded proteins. In this study, we show that sGFP, but not enhanced GFP, is functional in vivo at 70°C in the extreme thermophile Thermus thermophilus ( Tth ); thus, permitting the use of sGFP as a localization tag in vivo . We created a suite of plasmids that allow the expression of carboxy‐terminal sGFP fusion proteins in both Escherichia coli and Tth . In order to demonstrate the facility of sGFP as an in vivo localization tag in Tth , we tagged GroES (the small subunit of the bacterial GroES/GroEL chaperone), NarC (a membrane component of the nitrate respiration apparatus) and PhoA (a TAT‐secreted periplasmic protein), and visualized the distribution of the sGFP fusion proteins using confocal microscopy. Fusions to NarC and PhoA produced enzymatically active proteins that complemented both the narC and the phoA strains respectively. Observation of the distribution of the GroES‐sGFP protein by confocal microscopy revealed a homogeneous fluorescence in the cells, which is in full agreement with the cytoplasmic nature of GroES, whereas the NarC‐sGFP protein was localized to the membrane. Finally, a combination of confocal microscopy and biochemistry revealed that PhoA is localized in the periplasm. We suggest that sGFP will be broadly applicable in characterizing various extreme thermophile systems.

The role of the nitrate respiration element of Thermus thermophilus in the control and activity of the denitrification apparatus - Felipe Cava; Olga Zafra; Milton S. Da Costa; José Berenguer (Environmental Microbiology, 2008)
Summary The nitrate conjugative element (NCE) encodes the ability to respire nitrate in the facultative Thermus thermophilus NAR1 strain. This process is carried out by two heterotetrameric enzymes that catalyse the oxidation of NADH (Nrc) and the reduction of nitrate (Nar), whose expression is activated by the NCE‐encoded transcription factors DnrS and DnrT. We report the presence of NCE in other facultative strains of T. thermophilus and analyse its role in subsequent steps of the denitrification pathway. We encountered that nrc mutants of denitrifying strains show a decrease in anaerobic growth rates not only with nitrate, but also with nitrite, NO and N 2 O, which is concomitant to their lower NADH oxidation activities in vitro . We show that nitrate, nitrite and NO are activating signals for transcription of nrc in these strains. Finally, we demonstrate that DnrS and DnrT are required for anaerobic growth not only with nitrate, but also with nitrite, NO and N 2 O. These data allow us to conclude that: (i) Nrc constitutes the main electron donor for the four reductases of the denitrification pathway, and (ii) the NCE controls the expression of the whole denitrification pathway and the repression of the aerobic respiration through the transcription factors DnrS and DnrT.

The periplasmic space in Thermus thermophilus : evidence from a regulation-defective S-layer mutant overexpressing an alkaline phosphatase - Pablo Castán; Olga Zafra; Renata Moreno; Miguel de Pedro; Cristina Vallés; Felipe Cava; Eddy Caro; Heinz Schwarz; José Berenguer (Extremophiles, 2002)